Jumlah sel makrofag gingiva tikus wistar jantan yang diinduksi periodontitis setelah pemberian ekstrak etanolik kulit manggis Amount of machropahges cells in periodontitis-induced wistar rats after mangosteen rind etanolic extract administration - Rendra Chriestedy Prasetya (Journal of Dentomaxillofacial Science, 2013)
Periodontitis is characterized with macrophages infiltration that is used to fagocyt bacteria which infiltrated atgingiva. Mangosteen rind contains xantone, an anti-inflammatory substance which inhibits the synthesis of PGE2 andtherefore reduce inflammatory cells infiltration. This research aimed to study machropahges cells infiltration inperiodontitis-induced wistar rats after administration of mangosteen rind etanolic extract. Forty eight male wistar ratswere induced periodontitis for 7 days. After the ligation was taken out, the rats were divided into 4 groups, and treatedorally with mangosteen rind extract 60 mg/kg BB, 30 mg/kg BB, ibuprofen and saline. The rats were sacrified on the 1st, 3rd, 4th, and 7th day after the treatment. Their anterior lower jaws were processed histologically and stained withhematoxylin eosin. Two-way anova test showed a significant difference among groups (p<0.05). It was concluded thatmangosteen rind etanolic extract reduced the number of macropaghes cells gingiva in periodontitis male wistar rats.